2016
DOI: 10.1083/jcb.2133oia94
|View full text |Cite
|
Sign up to set email alerts
|

Continuous inhibitory signaling by both SHP-1 and SHIP-1 pathways is required to maintain unresponsiveness of anergic B cells

Abstract: , via SH2 binding, and activation of Lyn. Upon dual phosphorylation, ITAMs become docking sites for the kinase Syk that, in turn, is activated by phosphorylation, leading to phosphorylation of several downstream targets and culminating in B cell activation (Packard and Cambier, 2013). Whereas Lyn plays a role in B cell activation, it also propagates activity of regulatory signaling pathways by, for example, phosphor-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…62,63 Inducible deletion of PTEN is also sufficient to break tolerance of Ars/A1 B cells, although unlike anergic IgHEL B cells, PTEN itself is not overexpressed in this more modestly self-reactive model. 64 These findings may be generalizable to non-Tg B cells; Cambier and colleagues recently showed that PTEN expression varied continuously across the normal human B cell repertoire and correlated with increasing anergy and decreasing IgM expression. 65 More recently, Shlomchik and colleagues identified PTEN overexpression in GC B cells, which serves to redirect AKT kinase activity toward negative regulators of proximal BCR signaling, thereby engaging a negative feedback loop.…”
Section: Bcr Tg Mouse Modelsmentioning
confidence: 90%
“…62,63 Inducible deletion of PTEN is also sufficient to break tolerance of Ars/A1 B cells, although unlike anergic IgHEL B cells, PTEN itself is not overexpressed in this more modestly self-reactive model. 64 These findings may be generalizable to non-Tg B cells; Cambier and colleagues recently showed that PTEN expression varied continuously across the normal human B cell repertoire and correlated with increasing anergy and decreasing IgM expression. 65 More recently, Shlomchik and colleagues identified PTEN overexpression in GC B cells, which serves to redirect AKT kinase activity toward negative regulators of proximal BCR signaling, thereby engaging a negative feedback loop.…”
Section: Bcr Tg Mouse Modelsmentioning
confidence: 90%
“…33 Adoptive transfer of anergic B cells with subsequent induction of gene expression further showed that the inhibitory signaling pathways involved a tyrosine phosphatase SHP-1 and inositol phosphatase SHIP-1, which are both required to maintain anergy. 34 Activation events that disrupt anergy lead to rapid cell activation, proliferation, and short-lived plasma cells that reside in extrafollicular foci. 34 Previous studies by Goodnow and coworkers showed similar anergy loss in mice lacking Lyn, SHP-1, and CD22.…”
Section: Preg Erminal Center S Tag E B-cellmentioning
confidence: 99%
“…34 Activation events that disrupt anergy lead to rapid cell activation, proliferation, and short-lived plasma cells that reside in extrafollicular foci. 34 Previous studies by Goodnow and coworkers showed similar anergy loss in mice lacking Lyn, SHP-1, and CD22. The mechanistic basis was found to be phosphorylation of CD22 by Lyn, which then recruits SHP-1 to the CD22/BCR complex.…”
Section: Preg Erminal Center S Tag E B-cellmentioning
confidence: 99%
“…This defective BCR signalling results in reduced lifespan of the anergic B cells, altered migration and anatomical localization, and an inability to interact productively with helper T cells. Continuous inhibitory signalling pathways through tyrosine phosphatase Src homology region 2 1 domaincontaining phosphatase-1 (SHP-1) and the SH2-domaincontaining inositol phosphatase (SHIP-1) are required to maintain anergy, and inhibition of either of these pathways restored B cell activation, proliferation and generation of short-lived plasma cells [67]. Finally, anergic B cells have been reported as having an immature T3 [IgM mid , CD80 hi , CD95 hi , major histocompatibility complex (MHC) class II hi ] or a preplasma phenotype depending on the BCR specificity as well as ligand quality and quantity [60].…”
Section: Anergy and Regulation As Mechanisms Of B Cell Tolerancementioning
confidence: 99%